Consultation with epsicopal vicar before appointing a pastor: Canon 524 - Renken, John A. (Roman Replies and CLSA Advisory Opinions 2011, 2011)
"All the parishes of our diocese are grouped into four vicariates, each served by a "regional" episcopal vicar. Canon 524 refers to the diocesan bishop judging the suitability of a candidate for pastor by hearing the vicar forane and, if the case warrants it, also some presbyters and lay persons. Since we do not have vicars forane but episcopal vicars instead, must the diocesan bishop hear the regional episcopal vicar before appointing a pastor? And, if he must hear the regional episcopal vicar, is the appointment of the pastor invalid if this consultation is not done?"